Diagnostic value of ultrasonography versus electrodiagnosis in ulnar neuropathy - Rayegani SM (Dove Medical Press, 2019)
Seyed Mansoor Rayegani,1 Seyed Ahmad Raeissadat,2 Elham Kargozar,3 Shahram Rahimi-Dehgolan,3 Elham Loni4 1Physical Medicine and Rehabilitation Department and Research Center, Shohada-e-Tajrish Hospital, School of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Clinical Development Research Center of Shahid Modarres Hospital, Physical Medicine and Rehabilitation Department and Research Center, School of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Physical Medicine and Rehabilitation Department, School of Medicine, Tehran University of Medical Sciences (TUMS), Tehran, Iran; 4Physical Medicine and Rehabilitation Department, Rofaydeh Rehabilitation Hospital, University of Social Welfare and Rehabilitation Sciences, Tehran, Iran Purpose: Ulnar neuropathy at elbow is the second-most common compression neuropathy. The main aim of this study was to assess the diagnostic value of ultrasonography (US) as an alternative method to electrodiagnosis (EDX), which had traditionally been used as the method of choice.Methods: This diagnostic study was conducted on 66 participants (32 patients` elbows and 34 normal elbows) referred for EDX. Both groups were reassessed by US to evaluate the consistency of the two tests. The quantitative parameters of US, such as cross-sectional area (CSA) of the ulnar nerve at three different levels around the medial epicondyle (ME) were compared between groups.Results: Our findings demonstrated that CSA at the ME and 2 cm distal to the ME were significantly larger in the patient group than normal participants. This higher nerve size was more prominent among those who had predominant axonal loss rather than demyelinating lesions (P<0.01). Finally, we evaluated US diagnostic value with the best singular feature (2 cm distal to ME) at a cutoff of 9 mm2, which revealed specificity of 80% and sensitivity 84%.Conclusion: Based on these results we can conclude that US is a sensitive and specific method in diagnosing ulnar neuropathy at the elbow and can be used as an acceptable complementary method, in particular when EDX is not available. Keywords: Cubital Tunnel Syndrome, elbow, diagnostic tests, nerve compression syndromes, electromyography